A novel 'triple drawdown' method highlights deficiencies in invasive alien crayfish survey and control techniques. Issue 2 (12th October 2020) - Chadwick, Daniel D. A.; Pritchard, Eleri G.; Bradley, Paul; Sayer, Carl D.; Chadwick, Michael A.; Eagle, Lawrence J. B.; Axmacher, Jan C.
Abstract: Freshwater crayfish can be successful invaders that threaten native biota and aquatic ecosystems in numerous countries worldwide. Nonetheless, the inability of conventional crayfish survey techniques like trapping and handsearching to yield quantitative population data has limited the understanding of crayfish invasion biology and associated ecological impacts. Here, we employed a novel 'triple drawdown' (TDD) method to sample invasive populations of signal crayfish Pacifastacus leniusculus in a headwater stream in Northern England. The method was compared with conventional techniques of trapping and handsearching. The TDD method proved to be an effective technique with high capture efficiency, reporting signal crayfish densities from 20.5 to 110.4 animals/m 2 at our study sites. These numbers exceed any previous estimates for similar streams. The TDD showed the vast majority of individuals across all sites were juvenile or sub‐adult (<26 mm CL), with only 2.3% of the population large enough (≥35 mm CL) to be caught in standard traps. Synthesis and applications . The triple drawdown (TDD) method demonstrates strong inefficiencies and biases in conventional crayfish survey and management techniques. Trapping is not recommended for representative sampling or control of juvenile dominated populations. TDDs, which can be adapted and modified to operate in multiple habitat types and freshwater systems, generate robust quantitative data on invasive crayfish population demographics in situ. This can advance our understanding of the biology of an important invader of freshwater systems around the world. Obtaining this data prior and post‐intervention is fundamental to evaluate invasive crayfish management, and we recommend the TDD method to assess the effectiveness of future control measures. Abstract : The triple drawdown (TDD) method demonstrates strong inefficiencies and biases in conventional crayfish survey and management techniques. Trapping is not recommended for representative sampling or control of juvenile dominated populations. TDDs, which can be adapted and modified to operate in multiple habitat types and freshwater systems, generate robust quantitative data on invasive crayfish population demographics in situ. This can advance our understanding of the biology of an important invader of freshwater systems around the world. Obtaining this data prior and post‐intervention is fundamental to evaluate invasive crayfish management, and we recommend the TDD method to assess the effectiveness of future control measures.